Social Participation, In Gualalcay Leaders Community, According To The Elizabeth Anderson Model, Ethnographic Study, El Valle 2022 (The Review of Diabetic Studies, 2025)
The objective of the research is to describe the practices of social participation in leaders of the Gualalcay community, according to the Elizabeth Anderson model in the community of Gualalcay – El Valle Ecuador 2022. This is a qualitative, ethnographic study, carried out through interviews with depth to leaders of the Gualalcay community, which are recorded and transcribed for the respective analysis based on Elizabeth Anderson's nursing model. Citizen participation distributes power and improves living conditions; Elizabeth Anderson's model allows the practices of leaders to be systematized, identifying that actions improve the perception of community health and revealing the need for empowered communities, professionals trained in this right and discarding hegemonic paradigms, recognizing community wisdom.